Effects of high-intensity and moderate-intensity exercise training on cardiopulmonary function in patients with coronary artery disease: A meta-analysis - Zheng, Liying; Pan, Deng; Gu, Yimeng; Wang, Rumeng; Wu, Yanyan; Xue, Mei (Frontiers in Cardiovascular Medicine, 2022)
Purpose The study aims to evaluate the effects of high-intensity and moderate-intensity exercise training on cardiopulmonary function and exercise endurance in patients with coronary artery diseases (CAD). Methods We performed a systematic search of the English and Chinese databases from their inception to March 2022. Randomized controlled trials (RCTs) were included to compare high-intensity and moderate-intensity exercise training on cardiopulmonary function in patients with CAD. The primary outcomes included peak oxygen uptake (peak VO2) and anaerobic threshold (AT). The secondary outcomes included left ventricular ejection fraction (LVEF), exercises duration (ED), respiratory exchange ratio (RER), resting heart rate (RHR), peak heart rate (PHR) and oxygen pulse (O2 pulse). The continuous variables were expressed as mean differences (MD) along with their corresponding standard deviations (SD), and the I2 test was applied in the assessment of heterogeneity. Results After systematically literature search, 19 studies were finally selected for our meta-analysis (n = 1,036), with 511 patients in the experimental group (high-intensity exercise) and 525 patients in the control group (moderate-intensity exercise). The results showed that high-intensity exercise significantly increased patients' Peak VO2 [MD = 2.67, 95% CI (2.24, 3.09), P < 0.00001], LVEF [MD = 3.60, 95% CI (2.17, 5.03), P < 0.00001], ED [MD = 37.51, 95% CI (34.02, 41.00), P < 0.00001], PHR [MD = 6.86, 95% CI (4.49, 9.24), P < 0.00001], and O2 pulse [MD = 0.97, 95% CI (0.34, 1.60), P = 0.003] compared with moderate-intensity exercise. However, there were no significant differences in AT [MD = 0.49, 95% CI (−0.12, 1.10), P = 0.11], RER [MD = 0.00, 95% CI (−0.01, 0.02), P = 0.56], and RHR [MD = 1.10, 95% CI (−0.43, 2.63), P = 0.16]. Conclusion Our results show that high-intensity exercise training has more significant positive effects compared with moderate-intensity exercise training in improving peak VO2, LVEF, ED, PHR and O2 pulse in patients with CAD, while no significant differences were observed in AT, RER and RHR. To sum up, high-intensity exercise training is better than moderate-intensity exercise training in improving cardiopulmonary function and exercise endurance in patients with CAD. Systematic review registration PROSPERO (CRD42022328475), https://www.crd.york.ac.uk/PROSPERO/.